Biocosmological Role of Gauge Particles in the Origin of Chiral Life and the Inflationary Origin of Matter-antimatter asymmetry in Semiclosed Friedman Universe (Global Journal of Science Frontier Research, 2017)
The biocosmological role of CP-symmetry-violating chiral Z 0 boson in the origin of the chiral life and the cosmological role of CP-symmetric Higgs boson H 0 in the inflationary origin of the matter-antimatter asymmetry in the semiclosed Friedman universe are discussed.
Keywords: biology; cosmology; gauge particles; origin of life; matter-antimatter asymmetry